Factores de riesgo asociados al consumo de sustancias psicoactivas en los adolescentes del Colegio de Bachillerato Prócer José Picoita - Cruzpamba - Oviedo Oviedo, Paul Alexander (2022)
Drugs are substances that have the capacity to affect the normal functioning of the nervous system, causing serious consequences on the health of individuals; affecting their physical, mental and emotional state, the most vulnerable group being the juvenile population. The following investigation was to determine the risk factors associated with the consumption of psychoactive substances in adolescents of “Jose Picoita- Cruzpamba” High School. It was a quantitative, descriptive and cross-sectional study, the sample was made up of 61 students and for the data collection the psychological FRIDA was applied, the results determined that 69% of the respondents are in the age range of 16 to 18 years with female predominating, 99% are single; in relation to the risk factors associated with the use of psychoactive substances, it was determined that 34% of the cases, parents consume alcohol and 20% tobacco. Another factor found was the poor family relationship in 97% of respondents, 100% of the adolescents reported alcohol use, and 49% use tobacco because they find it easy to get alcohol, but harder to get heroine/cocaine. Finally, 26% have no healthy habits indicated not to engage in some type of physical activity. As a conclusion, the risk factors for the use of psychoactive substances are highlighted such as family conflicts, consumption of substances by parents, lack of information, availability to acquire this type of substances and consumption of alcohol and tobacco